PROBLEMATIKA RISK AND RETURN DALAM PERBANKAN SYARIAH - Yuli Afriyandi (As-Salam: Jurnal Studi Hukum Islam & Pendidikan, 2013)
The knowledge about risk in an investation is the important thing. Decisionof investaion for the investor is regarded the era that will come is unclear,it is contains a risk for inverstor. In order that in Islamic perspective, basicinvestation that needs to know in the institution of Islamic inance syariah such as bank that also place to invest fund. In the system of Islamic economy, ionvestation can decrease the poverty and increase the income with a way to bene it the wealth productively. The investation activity which agrees with Islamic syariah is the effort to produce the better life (falah), giving the bene its (maslahah) and keeping away the way of forbidden investation, that is riba, gharar, and maysir. But, productive investation can be implemented with the cooperation and proffessional in doing the main principle of syariat. The control of risk in banking industry is the main part for investor to invest. The management of this risk includes identi icating risk, measuring risk, managing risk, limiting risk, and observing risk. Through this approach the risk and the taking advantange can be measured. So the investor will get the chance return or value of sharing resulit optimally and also prospectively. The indeterminancy level of risk and return of result are the challenge its self to the syariah banking. The validity of law “hish risk brings about high return”forces syariah banking to apply the manage the risk that is more superior from conventional banking. So that the syariah banking must create a team that is able to manage and that is the include of the menegement of risk its self.